PERAN LINGKUNGAN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. WINDU RAYA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Agam, Gitra; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
This study aimed to analyze the variable influence of the Role of the Work Environment and Incentives on Employee Performance at PT Windu Raya, with Job Satisfaction as an Intervening Variable, by using the Partial Least Square (PLS) Structural equation model. The results of the direct effect hypothesis test using the Smart PLS 3.0 application. The work environment has a significant positive effect on job satisfaction (H1 accepted), incentives have a significant positive effect on job satisfaction (H2 accepted), the work environment has a positive but insignificant effect on employee performance (H3 rejected), incentives have a positive but insignificant effect on employee performance (H4 rejected), job satisfaction has a significant positive effect on employee performance (H5 accepted), the work environment has a significant positive effect on employee performance through job satisfaction (H6 accepted), and incentives have a significant positive effect on employee performance through job satisfaction (H7 accepted).